NASIONALISASI DAN PRIVATISASI DALAM PERSPEKTIF EKONOMI ISLAM - Riva’i, Yahya; Prawiro, Atmo (An Nawawi, 2023)
The liberal economic system is an economic system that is widely used in world countries. This economic system will spur people to try to create economic success but then what arises is a system of capitalism, resource monopoly, oligopoly etc.; then the state is present to try to equalize and regulate the dynamics of the country's economy and is known as socialism. And in terms of control over economic resources, Islamic economic thinkers have actually discussed this matter-which provides an explanation regarding the concept of ownership, control over economic resources and the presence of the state as a regulator. In this study, researchers examined the concept of ownership, control of economic resources and the presence of the state, in the perspective of Islamic Economics as contained in turat books. The purpose of this research is to provide an understanding of the community as Economic Actors, so that the economic activities they carry out are correct according to Islamic law. This research is a normative juridical research that uses a type of Syara'-Fiqh approach (statue approach), case approach (case approach) and conceptual approach (concept approach).